The Effect of The Board of Commissioners Structure on Dividend Policy : Study of The Non-Financial Family Firm in Indonesia Period 2017-2020 - Ayu Pita Winarti; Ernie Hendrawaty; R.A Fiska Huzaimah (Economic and Bussiness Faculty, Dr Soetomo University, 2022)
This study intends to research the impact of the board of commissioners structure along with the control variables of return on assets, debt level, firm size, firm growth, and the existence of other priority stackholders on family firm’s dividend policy in Indonesia’s non-financial sector. The research uses panel regression of 116 IDX non-financial listed family firm over the period 2017-2020. In order to explore the effects of board independence, family board, board size, board meeting frequency, and audit committee size on family firms’s dividend policy in non-financial sector in Indonesia. According to the study's findings, for the years 2017 to 2020, the dividend policy of family firm in Indonesia operating in non-financial sectors will be positively and significantly impacted by board independence, board presence from family, the board size, board meeting frequency, and audit committee size.